Molecular Profiling: A Case of ZBTB16-RARA Acute Promyelocytic Leukemia - Stephen E. Langabeer; Lisa Preston; Johanna Kelly; Matt Goodyer; Ezzat Elhassadi; Amjad Hayat (Case Reports in Hematology)
Several variant RARA translocations have been reported in acute promyelocytic leukemia (APL) of which the t(11;17)(q23;q21), which results in a ZBTB16-RARA fusion, is the most widely identified and is largely resistant to therapy with all-trans retinoic acid (ATRA). The clinical course together with the cytogenetic and molecular characterization of a case of ATRA-unresponsive ZBTB16-RARA APL is described. Additional mutations potentially cooperating with the translocation fusion product in leukemogenesis have been hitherto unreported in ZBTB16-RARA APL and were sought by application of a next-generation sequencing approach to detect those recurrently found in myeloid malignancies. This technique identified a solitary, low level mutation in the CEBPA gene. Molecular profiling of additional mutations may provide a platform to individualise therapeutic management in patients with this rare form of APL.